Status stres psikososial dan hubungannya dengan status gizi siswa SMP Stella Duce 1 Yogyakarta - Mutiara Tirta Prabandari Lintang Kusuma; Ronny Tri Wirasto; Emy Huriyati (Jurnal Gizi Klinik Indonesia, 2010)
Background: Adolescent is a transition phase from childhood to adulthood that marked by the change on physical, mental and psychosocial aspect. Adaptation on the change that people met in their life is called psychosocial stress. Stress makes a change on food habit and a disturbance on nutrition’s absorbance. Those circumstances affect people’s nutritional status.Objectives: To identify the correlation between psychosocial stress and nutritional status among SMP Stella Duce 1 Yogyakarta’s students.Methods: This study was an observational study which used a cross sectional design. It held by quantitative approach to identify the relationship between psychosocial stress and nutritional status. Subject of the study were 85 students of SMP Stella Duce 1 Yogyakarta. Respondent’s identities were collected by using identity questionnaire. Psychosocial stress’s status was collected by using SRRS questionnaire (social readjustment rating scale) that was modified for adolescent. Respondent’s calories intakes were assessed by using the form food recall 3 x 24 h. Anthropometrics data collected were weight and height. The adjustment of psychosocial stress’s status used SRRS questionnaires. Calories intake were measured by using nutrition software (Fp2). Student’s nutritional status was measured by using Epi 2000 software. Relationship’s analysis among variables uses statistical test of SPSS 12.00, with the correlation or linear regression test.Result: From this study, 49.4% (42 people) have normal nutritional status, 4.7 % at under nutrition level, 25.9% at risk of obesity, and 20% obesity. From the measurement of psychosocial stress’s score, there were 61.2% (52 people) in a non-tress condition, while the other was on stress at different level. Statistical test showed that there was no relationship between psychosocial stress and nutritional status (p > 0.05).Conclusion: There was no significant relationship between psychosocial stress and nutritional status among SMP Stella Duce 1 Yogyakarta’s students.